Primeras jornadas de lengua y literatura hispanoamericana. Acta Salmanticensia, Salamanca, 10 (1956); 2 ts.: 500 y 346 pp. - Mejía Sánchez, Ernesto (El Colegio de México, 2007)
Se reseñó: Primeras jornadas de lengua y literatura hispanoamericana. Acta Salmanticensia, Salamanca, 10 (1956); 2 ts.